Micropatterned nanocomposite hydrogels for biosensing applications - Pedrosa, Valber A. [UNESP]; Yan, Jun; Simonian, Aleksandr L.; Revzin, Alexander (Wiley, 2011)
This paper describes the use of Au nanoparticle (NP)-containing hydrogel microstructures in the development of electrochemical enzyme-based biosensors. To fabricate biosensors, AuNPs were conjugated with glucose oxidase (GOX) or horseradish peroxidase (HRP) molecules and were dispersed in the prepolymer solution of poly(ethylene glycol) diacrylate (PEG-DA). Vinylferrocene (VF) was also added into the prepolymer solution in order to lower operating potential of the biosensor and to prevent oxidation of interfering substances. The prepolymer solution was photolithographically patterned in alignment with an array of Au electrodes fabricated on glass. As a result, electrode arrays became functionalized with AuNP/GOX- or AuNP/HRP-carrying hydrogel microstructures. Performance of the biosensors was characterized by impedance spectroscopy, chronoapmerometry and cyclic voltammetry. Impedance measurements revealed that inclusion of Au nanoparticles improved conductivity of PEG hydrogel by a factor of 5. Importantly, biosensors based on AuNP-GOX complex exhibited high sensitivity to glucose (100μAmM -1cm -2) in the linear range from 0.1 to 10mM. The detection limit was estimated to be 3.7×10- 7M at a signal-to-noise ratio of 3. Biosensors with immobilized AuNP/HPR had a linear response from 0.5 to 5.0μM of hydrogen peroxide with sensitivity of 1.4mAmM -1cm -2. The method for fabricating nanoparticle-carrying hydrogel microstructures described in this paper should be widely applicable in the development of robust and sensitive electrochemical biosensors. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Glucose oxidase; Gold nanoparticles; HPR; Hydrogel